Creating or awakening national pride through sporting success: A longitudinal study on macro effects in the Netherlands - Elling, A.; van Hilvoorde, I.; van den Dool, R. (International Review for the Sociology of Sport, 2014)
Like many other countries, the Dutch government increased investments in elite sports in the last decennium, partly driven by the ambition to organise the Olympic Games in 2028 in the Netherlands. One of the most important legitimations for this ambition is that elite sports events and national achievements should foster national pride, social cohesion and international prestige.